A brGDGT-based reconstruction of terrestrial temperature from the Maritime Continent spanning the Last Glacial Maximum - Meredith Parish (PANGAEA, 2022)
We present a 60,000-yr long temperature reconstruction based on branched glycerol dialkyl glycerol tetraethers (brGDGT) in a sediment core from Lake Towuti, located in Sulawesi, Indonesia. brGDGTs were measured in one sample very 500 years. In 2020, we analyzed the samples using atmospheric pressure chemical ionization/high-performance liquid chromatography mass spectrometry (APCI/HPLC-MS) with a bridged ethylsiloxane/silica hybrid (BEH) hydrophilic interaction chromatography (HILIC) 1.7 um (2.1 x 150 mm) column using selective ion monitoring mode, targeting molecules at m/z 1050, 1048, 1046, 1036, 1034, 1032, 1022, 1020, 1018, 1292, 1296, 1298, 1300, and 1302 (Hopmans et al., 2016). The timing of the deglacial warming in our record occurs after the onset of the deglacial increase in atmospheric CO2 concentrations, which suggests rising greenhouse gas concentrations and the associated radiative forcing may have forced deglacial warming in the IPWP. Peaks in temperature around 55 ka and 34 ka indicate that Northern Hemisphere summer insolation may also influence land surface temperature in the IPWP region.